2020
DOI: 10.7224/1537-2073.2018-090
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Sclerosis Self-Management Scale–Revised (MSSM-R)

Abstract: Background: Self-management is the most important component in the treatment of chronic diseases, including multiple sclerosis (MS). The Bishop and Frain Multiple Sclerosis Self-Management Scale–Revised (MSSM-R) is one of the valid tools available for self-management assessment. The purpose of this study was to evaluate the psychometric properties of the MSSM-R in Iranian people with MS. Methods: This cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The results of the structural validity showed that this instrument was significantly negatively correlated with Multiple Sclerosis Impact Scale, and significantly positively correlated with Multiple Sclerosis Self-Efficacy scale, indicating the divergent and convergent validity of this instrument (15). The Persian version of MSSM-R has been shown to have adequate reliability and validity (14). The internal consistency for this scale based on Cronbach's alpha was 0.78.…”
Section: Measurement Toolsmentioning
confidence: 91%
See 1 more Smart Citation
“…The results of the structural validity showed that this instrument was significantly negatively correlated with Multiple Sclerosis Impact Scale, and significantly positively correlated with Multiple Sclerosis Self-Efficacy scale, indicating the divergent and convergent validity of this instrument (15). The Persian version of MSSM-R has been shown to have adequate reliability and validity (14). The internal consistency for this scale based on Cronbach's alpha was 0.78.…”
Section: Measurement Toolsmentioning
confidence: 91%
“…The investigation of epidemiological studies shows that MS is common in Iran. The prevalence of MS in Guilan Province (GP), is estimated to be approximately 33.7 patients per 100,000 population (14); Considering that self-management behaviors and PC have been introduced as the most important factors in healthpromoting behaviors, it is necessary to investigate the role of these factors in predicting NB in a single study. therefore, this study aimed to investigate the direct and indirect effect of self-management on NB with the mediating role of PC.…”
mentioning
confidence: 99%
“…However, the method used was not clearly described. The comprehensibility of Persian [32], Polish [33], and Turkish [31] versions of this instrument was also assessed, but either the target population did not participate in the assessment [31,32], or the methodology was not clearly described [33]. Regarding the RIKNO 2.0 questionnaire, the content validity study only assessed the comprehensibility of its translated versions.…”
Section: Content Validitymentioning
confidence: 99%
“…Findings on the structural validity of the MSSM scale-revised were inconsistent. The confirmatory factor analysis of a five-factor structure showed a good model fit in one study [32] and a poor model fit in another [33] (Supplementary Table A). Only three instruments showed sufficient evidence for structural validity: the MSSM-2 scale, the Patient Activation Measure (PAM), and the PAM short form (Table 5).…”
Section: Construct Validitymentioning
confidence: 99%
“…The fact that MS affects neurotransmitter systems and structures (like the amygdala, basal ganglia, and cerebral cortex [ 10 ]) involved in the processing and perception of emotions [ 11 ] supports the notion that symptoms of anxiety and depression, as well as the decline in psychological well-being observed among PwMS, have a biological etiology [ 12 ]. Accordingly, the results of previous studies show that PwMS in Guilan province suffer from a variety of psychological disorders compared to their healthy counterparts [ 13 , 14 ]. Given all this evidence, a concentration on factors determining the psychological well-being in PwMS can be very consequential [ 15 ].…”
Section: Introductionmentioning
confidence: 99%